ANTIBACTERIAL ACTIVITY OF ETHANOLIC EXTRACT OF SELIGI LEAVES (Phyllanthus buxifolius (BLUME) MULL. ARG) AGAINST THE GROWTH OF Staphylococcus epidemicdis ATCC 12228: Antibacterial Potential of Ethanol Extract of Seligi Leaves (Phyllanthus buxifolius (Blume) Mull. ARG) Against Staphylococcus epidermidis ATCC 12228 in Vitro - Yeliza, Adniana; Kusniawati, Mega Ayu; Hamidu, La; Oktariyana, Hani (JFL : Jurnal Farmasi Lampung, 2025)
By interfering with the metabolism of these dangerous germs, antibacterial compounds may hinder, combat, and ultimately destroy the development of microbes. Finding out how effective seligi leaf ethanol extract is against Staphylococcus epidermidis bacteria and what dosage produces the optimal inhibitory zone are the primary goals of this research. Maceration with a 96% ethanol solvent was used to extract the Seligi leaves. Each of the five groups underwent the test three times: those receiving a negative control (aquadest), those receiving a positive control (clindamycin 5%), and those receiving nutritional agar medium containing 25%, 50%, or 75% seligi leaf extract. Using a caliper, the antibacterial activity test determined the inhibitory zone diameter in millimeters.To find out how the different treatment groups differed, the collected data were subjected to analysis of variance and post hoc LSD. Antibacterial action against the development of Staphylococcus epidermidis was shown by the findings of ethanol extracts of seligi leaves at concentrations of 25%, 50%, and 75%. With an average inhibition diameter of 7.53 mm, the most active component was a 75% ethanol extract of seligi leaves, was on par with the positive controls. Keywords:  Antibacterial, seligi leaf extract, diameter of inhibition zone